2009
DOI: 10.1007/s11430-009-0087-y
|View full text |Cite
|
Sign up to set email alerts
|

Soil water depletion depth by planted vegetation on the Loess Plateau

Abstract: Evapotranspiration of much planted vegetation exceeds precipitation, and this can deplete soil water and cause a deep dry layer in the soil profile, which is a serious obstacle to sustainable land use on the Loess Plateau, China. This study aimed to determine water depletion depth of planted grassland, shrub, and forest in a semiarid area on the Loess Plateau. Soil moisture of five vegetation types was measured to >20 m in depth. The vegetation types were crop, natural grasse, seven-year-old planted alfalfa (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(75 citation statements)
references
References 10 publications
2
71
1
1
Order By: Relevance
“…Furthermore, no differences in soil moisture in deep soil layers appeared between different introduced vegetations (Table 3). Previous studies found that the deep soil moisture differed significantly between traditional farmland or native grassland solely and introduced vegetation Wang et al, 2011bWang et al, , 2009c. In this study, although the soil moisture in deep layers varied with different introduced vegetation covers, the difference was not statistically significant among the six vegetation types that were introduced.…”
Section: Land Use Subclassescontrasting
confidence: 72%
“…Furthermore, no differences in soil moisture in deep soil layers appeared between different introduced vegetations (Table 3). Previous studies found that the deep soil moisture differed significantly between traditional farmland or native grassland solely and introduced vegetation Wang et al, 2011bWang et al, , 2009c. In this study, although the soil moisture in deep layers varied with different introduced vegetation covers, the difference was not statistically significant among the six vegetation types that were introduced.…”
Section: Land Use Subclassescontrasting
confidence: 72%
“…Scientists, policy makers and land managers require information to support their decisions involving land use and options of plant species. The ecological restoration on the Loess Plateau and other water-limited regions around the world requires a systematic consideration of (1) the dynamics of water both in time and space, (2) the transportation of water in the soil-plant-atmosphere continuum and (3) the planning of sustainable land uses (Wang et al, 2009). Choosing reasonable land-use patterns and suitable species are thus crucial because the shortage of water is a key factor.…”
Section: Aboveground Biomass Of C Korshinskii and Grasslandmentioning
confidence: 99%
“…Considerable interest has since been generated around the world in the assessment of vertical distribution and influencing factors Yang et al, 2012), depletion and replenishment (Li and Huang, 2008;Liu et al, 2010), dynamics and simulations (Jipp et al, 1998;Markewitz et al, 2010;Zhao et al, 2008) of SWC in soils to a depth of roughly 1000 cm. The depth of depletion of SWC, inferred to be a function of root uptake, has recently been reported to be 1800 cm in an Amazonian forest (Davidson et al, 2011) and to be 1550, 2240 and 2150 cm (based on the comparison of soil-water conditions between shrublands/forests and permanent farmland) in alfalfa grassland, Caragana korshinskii shrubland and pine forest, respectively, on the Loess Plateau of China (Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Jiao et al (2011) reported that soil nutrition, such as soil organic matter and total nitrogen decreased during the early stage of vegetation restoration after farmland abandonment on the Loess Plateau. Wang et al (2009) found that tree planting on a former farmland caused an obvious decline in soil water content and led to the formation of a dried soil layer in the arid area.…”
mentioning
confidence: 99%